Persepsi ahli politik Pulau Pinang terhadap perlaksanaan dasar-dasar Islam di Pulau Pinang selepas PRU 12 / Zulkifli Dahalan and Mohd Hapiz Mahaiyadin - Mahaiyadin, Mohd Hapiz; Dahalan, Zulkifli (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2012)
After the 12th general election, Penang is ruled by the opposition party. The enormous win by DAP has enabled them to be in the lead in Penang. Unfortunately, the number of Malay candidates representing PAS and PKR did not achieve an encouraging win. Consequently, the number of Malay representatives in the EXCO has dropped significantly as compared to the one when GERAKAN, together with UMNO, was in the lead. It has become an issue especially when relating to matters regarding Islam in the politics of Penang. DAP has always been known to champion a specific race passionately and to be cynical towards any issues pertaining to Islam. Till now, the mass media have been playing their role to negatively slam DAP figures relating to Islamic matters. The matters have worsened when there are certain quarters that have voiced their worries about the undertakings of Islam and Malays. This study aims to illustrate the views of various party leaders, government agency leaders and religious leaders regarding the issue.